The merits of teaching local history: Increased place attachment enhances civic engagement and social trust. (August 2017) - Stefaniak, Anna; Bilewicz, Michał; Lewicka, Maria
Abstract: Low levels of civic engagement and social trust in post-communist countries constitute an important limitation to national economic growth and the well-being of inhabitants. In the current paper we propose that discovering local history should result in greater place attachment which constitutes a viable strategy for stimulating indicators of social capital. Specifically, we tested the influence of teaching local history on the development of interest in history, place attachment, and civic engagement. Two intervention studies ( N 1  = 486; N 2  = 1098) confirmed that young people who learned about local history displayed increased interest in that history, greater place attachment, civic engagement intentions, and generalized social trust. We also demonstrate the relevance of place attachment as a link between greater interest in local history and increased civic engagement. The importance of stimulating youth civic engagement and generalized social trust are discussed. Highlights: Teaching local history stimulates place attachment. Greater place attachment is associated with increased readiness for civic engagement. Local history as a new way to build social trust in Central Europe.